Cardiorespiratory and metabolic consequences of detraining in endurance athletes - Barbieri, A.; Fuk, A.; Gallo, G.; Gotti, D.; Meloni, A.; La Torre, A.; Filipas, L.; Codella, R. (Frontiers in Physiology, 2024)
Background: A training program can stimulate physiological, anatomical, and performance adaptations, but these improvements can be partially or entirely reversed due to the cessation of habitual physical activity resulting from illness, injury, or other influencing factors.